کاریگەریی ستراتیجێکی پێشنیازکراو پشتبەست بەدەستپێکی ڕ‌ێکخراوە هێڵکارییەکان لە بابەتی (Mathematical Analysis) لەسەر دەستکەوتی خوێندکاران - جمعە, پ.د.علی عبدالرحمن; عزیز, د.هەردی نصردین; امین, لاڤە حمەسوور محمد (Sulaimani Journal for Humanities, 2023)
The main objective of this research is to determine the effectiveness of a proposed strategy based on the start of graphic organizations in the subject of (Mathematical Analysis) on student achievement, the research sample consisted of (54) students divided in to two groups, the experimental group studied the subject according to the proposed strategy based on graphic organisations and the control group studied the subject in the traditional way. Six plans were prepared for each group, an achievement test consisting (18) sections was prepared, (7) sections of the true or false question type, (5) sections of the multiple-choice questions and (6) sections of the essay question. Face and Content Validity was discovered, the test reliability was found in the form of test -retest by conducting it on an exploratory sample consisting of (54) students excluding the students of the research sample they were tested again two weeks later, by using Person’s coefficient it was found to be (0.94), difficulty coefficient, discriminating power and effectiveness of distraction was found for multiple choice type questions. By using the T-test equation it was found that there was a statistically documented difference between the achievement of both groups in favour of the experimental group.